Preparation method and application of modified lignin composite film
By modifying lignin and biodegradable polymer materials, a fully biodegradable composite film with excellent mechanical properties and low production costs was prepared, which solved the shortcomings of existing fully biodegradable plastics in terms of mechanical properties and costs, and achieved its wide promotion in various application fields.
Patent Information
- Application Number
- CN202510066600.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The existing fully biodegradable plastics have shortcomings in mechanical properties and production costs, which limits their large-scale promotion and application in agriculture and daily necessities.
Fully biodegradable composite films are prepared by composite modified lignin with PBAT, PHA, PLA, PCL or PBS. The mechanical properties of the composite films are enhanced and the production costs are reduced through the addition of modified lignin and the use of interface compatibility agents.
The prepared composite film has excellent mechanical properties, including high tensile strength, elastic modulus and elongation of break, and has low production costs. It is suitable for making plastic films, plastic wrap, vest bags or packaging bags.
Smart Images

Figure CN119751940A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fully biodegradable composite films, and in particular to a preparation method and application of a modified lignin composite film. Background Art
[0002] White pollution caused by the widespread use of plastics poses a serious threat to the environment and human health. Therefore, the development of a fully biodegradable plastic material to replace traditional non-degradable plastics has become an urgent problem to be solved. At present, the main fully biodegradable plastics on the market include PBAT, PHA, PLA, PCL and PBS, but their high production costs and poor mechanical properties limit their large-scale promotion and application in agriculture and daily necessities. Based on this situation, the present invention proposes a composite film material that is fully biodegradable and low-cost, prepared by using modified lignin as a filler and compounding with PBAT, PHA, PLA, PCL or PBS, which is expected to solve the current technical and industrial bottlenecks of fully biodegradable plastics. Summary of the invention
[0003] The purpose of the present invention is to provide a preparation method and application of a modified lignin composite film. Compared with PBAT, PHA, PLA, PCL or PBS films, the composite film prepared by the present invention not only overcomes the defects of the mechanical properties of traditional fully biodegradable films, but also ensures the blow molding of the composite film, and can be widely used in the production of ground films, cling films, vest bags or packaging bags.
[0004] To achieve the above object, the present invention provides a method for preparing a modified lignin composite film, comprising the following steps:
[0005] S1. Modification of aliphatic hydroxyl and phenolic hydroxyl groups of lignin: adding a modifier to lignin, and then reacting at 25°C to 160°C for 4-48 hours; after the reaction, dripping the solution into a solution with a pH of 2 to 4 to precipitate lignin, and obtaining modified lignin by centrifugation, washing, and freeze-drying;
[0006] S2, mixing and granulating: mixing the biodegradable polymer material and the modified lignin according to the mass ratio, adding an interfacial compatibilizer to the mixture, mixing evenly and putting into a twin-screw extruder for granulation to obtain a masterbatch;
[0007] S3, hot pressing film forming: hot pressing the masterbatch obtained by granulation in step S2 for 1-5 minutes at 120-180°C and 2-15MPa to obtain a composite film;
[0008] S4, film blowing: the masterbatch obtained by granulation in step S2 is blown into a film at 130-180°C.
[0009] Furthermore, the lignin in step 1 comprises one or a combination of alkali lignin, organic solvent lignin, DES lignin, ionic liquid lignin, sulfate lignin, lignin sulfonate and ground wood lignin.
[0010] Furthermore, in step 1, the modifier is a mixture of acetic anhydride, propionic anhydride or butyric anhydride, maleic anhydride, acyl chloride or polyethylene glycol and pyridine, and the volume ratio of acetic anhydride, propionic anhydride, butyric anhydride, maleic anhydride, acyl chloride or polyethylene glycol to pyridine is 1:1-5.
[0011] Furthermore, in step 1, the dosage ratio of lignin to modifier is 1g:5-10ml.
[0012] Furthermore, in step 2, the biodegradable polymer material is one or more of PBAT, PHA, PLA, PCL or PBS.
[0013] Furthermore, in step 2, the biodegradable polymer material accounts for 30-50% of the total mass of the biodegradable polymer material and the modified lignin, and the modified lignin accounts for 50-70% of the total mass of the biodegradable polymer material and the modified lignin.
[0014] Furthermore, in step 2, the interfacial compatibilizer accounts for 1-9% of the total mass of the masterbatch, and the interfacial compatibilizer includes one or a combination of dibutyl adipate, diisodecyl phthalate, dioctyl phthalate, triphenyl phosphate, tributyl citrate, trioctyl citrate, glycerol, polyethylene glycol, glucose, ethyl lactate, sodium benzoate, sodium lauryl sulfate, tannic acid, and Teflon 80.
[0015] The present invention also provides a modified lignin composite film, which is prepared by the above preparation method.
[0016] Furthermore, the tensile strength of the modified lignin composite film is ≥20 MPa, the elastic modulus is ≥200 MPa, and the elongation at break is ≥200%.
[0017] The present invention also provides the use of the modified lignin composite film in making ground film, fresh-keeping film, vest bag or packaging bag.
[0018] The present invention adopts the above-mentioned preparation method and application of a modified lignin composite film, and its beneficial effects are:
[0019] 1. The present invention modifies the phenolic hydroxyl group and aliphatic hydroxyl group of lignin to obtain modified lignin. The intermolecular force between the modified lignin and PBAT, PHA, PLA, PCL or PBS is enhanced. Compared with pure PBAT, PHA, PLA, PCL or PBS film, the composite film provided by the present invention has excellent mechanical properties.
[0020] 2. The present invention utilizes dibutyl adipate, diisodecyl phthalate, dioctyl phthalate, triphenyl phosphate, tributyl citrate, trioctyl citrate, glycerol, polyethylene glycol, glucose, ethyl lactate, sodium benzoate, sodium lauryl sulfate, tannic acid, and TWE 80 as interfacial compatibilizers. After the interfacial compatibilizer is added, the amount of modified lignin added to the composite film can reach 70%. The addition of the interfacial compatibilizer not only improves the interfacial bonding force between the modified lignin and the biodegradable polymer, but also promotes the dispersibility of the modified lignin in the biodegradable polymer, reduces stress concentration, and greatly improves the mechanical properties of the fully biodegradable composite film material.
[0021] 3. The composite film provided by the present invention has good mechanical properties, barrier properties and full biodegradability. It can not only be used as a ground film, but also can be used in the fields of vest bags, packaging bags or cling film. While maintaining the full biodegradability, it greatly reduces the production cost.
[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : The changes of soil temperature and humidity when rapeseed is covered with different mulch films in the embodiment of the present invention, wherein A is the change of soil humidity and B is the change of soil temperature. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0025] The present invention can be explained in more detail by the following examples. The purpose of disclosing the present invention is to protect all changes and improvements within the scope of the present invention. The present invention is not limited to the following examples.
[0026] Unless otherwise defined, the alkali lignin, organosolv lignin, DES lignin, ionic liquid lignin, kraft lignin, lignin sulfonate and groundwood lignin, PBAT, PHA, PLA, PCL or PBS used in the present invention are conventionally commercially available.
[0027] Unless otherwise defined, the reagents used in the present invention, such as dibutyl adipate, diisodecyl phthalate, dioctyl phthalate, triphenyl phosphate, tributyl citrate, trioctyl citrate, glycerol, polyethylene glycol, glucose, ethyl lactate, sodium benzoate, sodium lauryl sulfate, tannic acid, Tween 80, etc., are all conventionally commercially available.
[0028] Example 1
[0029] A method for preparing a modified lignin composite film comprises the following steps:
[0030] S1. Modification of aliphatic hydroxyl and phenolic hydroxyl groups of lignin: add a mixed solution of acetic anhydride and pyridine (50 mL: 50 mL) to 10 g of kraft lignin, and react at 25°C for 48 hours; after the reaction, drop the solution into a solution with a pH of 2 to 4, and then centrifuge the obtained mixed solution, wash with ultrapure water, and freeze-dry for 24 to 48 hours to obtain modified lignin.
[0031] S2, mixing and granulating: 40% by weight of PBAT and 10% by weight of PHA are mixed with 50% by weight of modified lignin to obtain a mixture, 3% by weight of tributyl citrate is added to the mixture as an interfacial compatibilizer, the mixture is mixed and stirred in a double planetary mixer, and then the mixture is granulated in a twin-screw extruder to obtain a masterbatch. The temperature of the twin screw is 130-175°C and the rotation speed is 20-33rpm / min.
[0032] S3. Hot pressing film forming: hot press the masterbatch at 140°C to 175°C and 2 to 15 MPa for 1 to 5 minutes to obtain a composite film.
[0033] S4, film blowing: blow the masterbatch into film at 135℃~175℃ and a rotation speed of 400-800rpm / min.
[0034] Example 2
[0035] A method for preparing a modified lignin composite film comprises the following steps:
[0036] S1. Modification of aliphatic hydroxyl groups and phenolic hydroxyl groups of lignin: a mixed solution of propionic anhydride and pyridine (propionic anhydride: pyridine = 30 mL: 40 mL) was added to 10 g of kraft lignin and reacted at 35°C for 36 h; after the reaction, the solution was dropped into a solution with a pH of 2 to 4, and the resulting mixed solution was then centrifuged, washed, and freeze-dried for 24 to 48 h to obtain modified lignin.
[0037] S2, mixing and granulation: 37% by weight of PBAT, 3% by weight of PLA and 60% by weight of modified lignin are mixed to obtain a master batch, 5% by weight of sodium dodecyl sulfate is added to the master batch as an interfacial compatibilizer, the mixture is mixed and placed in a double planetary agitator for stirring, and then the mixture is placed in a twin-screw extruder for granulation. The temperature of the twin screw is 130-175°C and the rotation speed is 20-33rpm / min.
[0038] S3. Hot pressing film forming: hot press the masterbatch at 140°C to 175°C and 2 to 15 MPa for 1 to 5 minutes to obtain a composite film.
[0039] S4, film blowing: blow the masterbatch into film at 130℃~175℃ and a rotation speed of 400-800rpm / min.
[0040] Example 3
[0041] A method for preparing a modified lignin composite film comprises the following steps:
[0042] S1. Modification of aliphatic hydroxyl groups and phenolic hydroxyl groups of lignin: polyethylene glycol is added to 10 g of organic solvent lignin, and the mixture is reacted at 150° C. for 6 h. After the reaction, the solution is dripped into a solution with a pH of 2 to 4, and the resulting mixed solution is centrifuged, washed, and freeze-dried for 24 to 48 h to obtain modified lignin.
[0043] S2, mixing and granulation: 40% by weight of PBAT and 60% by weight of modified lignin are mixed to obtain a mixture, 3% by weight of sodium dodecyl sulfate is added to the mixture as an interfacial compatibilizer, the mixture is mixed and placed in a double planetary mixer for stirring, and then the mixture is placed in a twin-screw extruder for granulation to obtain a masterbatch. The temperature of the twin screw is 130-170°C and the rotation speed is 20-33rpm / min.
[0044] S3. Hot pressing film forming: hot press the masterbatch at 140°C to 175°C and 2 to 15 MPa for 1 to 5 minutes to obtain a composite film.
[0045] S4, film blowing: blow the masterbatch into film at 130℃~170℃ and a rotation speed of 400-800rpm / min.
[0046] Comparative Example 1
[0047] The preparation method of the PBAT film comprises the following steps:
[0048] S1. Hot pressing film forming: hot pressing PBAT at 140°C to 150°C and 2 to 15 MPa to obtain a composite film.
[0049] Comparative Example 2
[0050] A method for preparing a lignin composite film comprises the following steps:
[0051] S1. Mixing and granulation: PBAT and lignin are mixed in a mass ratio of 1:1, and the mixed mixture is put into a twin-screw extruder for granulation to obtain masterbatch, wherein the temperature of the twin screw is 130-145°C and the rotation speed is 20-33rpm / min.
[0052] S2. Hot pressing film forming: hot pressing the masterbatch at 140°C to 150°C and 2 to 15 MPa for 1 to 5 minutes to obtain a composite film.
[0053] Performance Testing
[0054] The mechanical properties of the composite films (hot pressing films) prepared in Examples 1-3 and Comparative Examples 1-2 were tested. The results are shown in Table 1.
[0055] Table 1 Mechanical properties of composite membranes
[0056] Tensile strength(MPa) Elongation at break (%) Young's modulus (MPa) Example 1 25.4±0.8 297.6±17.6 218.1±20 Example 2 23.5±1.1 236.5±5.2 197.6±5.2 Example 3 20.2±1.2 306.5±12.6 203.5±10.5 Comparative Example 1 28.7±2.0 795.9±78.1 58.5±3.9 Comparative Example 2 21.3±1.2 100.3±2.9 245.4±28
[0057] As can be seen from Table 1, the tensile strength and elongation at break of Comparative Example 2 are lower than those of Comparative Example 1, while the Young's modulus is much higher than that of Comparative Example 1, indicating that the addition of lignin can increase the Young's modulus, but the tensile strength and elongation at break will decrease.
[0058] To solve this problem, modified lignin is added in the examples. Compared with Comparative Example 2, Examples 1 and 2 add modified lignin and an interfacial compatibilizer to promote the fusion between the two phase interfaces, which not only maintains the Young's modulus at a high level, but also improves the tensile strength and elongation at break. This shows that the modified lignin composite film overcomes the defect of the traditional PBAT film being too flexible, ensures both blow molding and strength, and greatly reduces the cost.
[0059] Therefore, the present invention adopts the above-mentioned preparation method and application of a modified lignin composite film. Compared with PBAT, PHA, PLA, PCL or PBS films, the fully biodegradable composite film prepared by the present invention has excellent mechanical properties. The composite film not only overcomes the defects of the mechanical properties of traditional fully biodegradable films, but also ensures the blow molding of the composite film, and can be widely used in the production of ground film, cling film, vest bag or packaging bag.
[0060] Application Examples
[0061] The fully biodegradable film prepared in Example 1 was used as the experimental material for the actual application of film covering rapeseed, cabbage, tomato, corn and cotton. Taking rapeseed as an example, the changes in soil temperature and humidity after film covering are shown in the figure. Figure 1 As shown, from Figure 1 It can be seen that the thermal insulation and entropy increasing performance of the fully biodegradable composite membrane of Example 1 are better than those of the traditional fully biodegradable PBAT membrane and close to those of the PE membrane, which proves the application potential of the composite membrane in ground membrane.
[0062] Finally, it should be noted that the above embodiments and application examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a modified lignin composite film, characterized in that: The following steps are involved: S1. Modification of aliphatic hydroxyl and phenolic hydroxyl groups of lignin: adding a modifier to lignin, and then reacting at 25°C to 160°C for 4-48 hours; after the reaction, dripping the solution into a solution with a pH of 2 to 4 to precipitate lignin, and obtaining modified lignin by centrifugation, washing, and freeze-drying; S2, mixing and granulating: mixing the biodegradable polymer material and the modified lignin in proportion, adding an interfacial compatibilizer to the mixture, mixing evenly, and granulating through a twin-screw extruder to obtain a masterbatch; S3, hot pressing film forming: hot pressing the masterbatch obtained in step S2 at 120-180° C. and 2-15 MPa for 1-5 min to obtain a composite film; S4, film blowing: the masterbatch obtained in step S2 is blown into a film at 130-180°C.
2. The method for preparing a modified lignin composite film according to claim 1, characterized in that: The lignin in step 1 includes one or a combination of alkali lignin, organic solvent lignin, DES lignin, ionic liquid lignin, sulfate lignin, lignin sulfonate or ground wood lignin.
3. The method for preparing a modified lignin composite film according to claim 1, characterized in that: In step 1, the modifier is a mixture of acetic anhydride, propionic anhydride, butyric anhydride, maleic anhydride, acyl chloride or polyethylene glycol and pyridine, and the volume ratio of acetic anhydride, propionic anhydride, butyric anhydride, maleic anhydride, acyl chloride or polyethylene glycol to pyridine is 1:1-5.
4. The method for preparing a modified lignin composite film according to claim 1, characterized in that: In step 1, the dosage ratio of lignin to modifier is 1g:5-10ml.
5. The method for preparing a modified lignin composite film according to claim 1, characterized in that: The biodegradable polymer material in step 2 includes one or more of PBAT, PHA, PLA, PCL, and PBS.
6. The method for preparing a modified lignin composite film according to claim 1, characterized in that: In step 2, the biodegradable polymer material accounts for 30-50% of the total mass of the biodegradable polymer material and the modified lignin, and the modified lignin accounts for 50-70% of the total mass of the biodegradable polymer material and the modified lignin.
7. The method for preparing a modified lignin composite film according to claim 1, characterized in that: In step 2, the interfacial compatibilizer accounts for 1-9% of the total mass of the masterbatch, and the interfacial compatibilizer includes one or a combination of dibutyl adipate, diisodecyl phthalate, dioctyl phthalate, triphenyl phosphate, tributyl citrate, trioctyl citrate, glycerol, polyethylene glycol, glucose, ethyl lactate, sodium benzoate, sodium lauryl sulfate, tannic acid, and Teflon 80.
8. A modified lignin composite film, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. A modified lignin composite film according to claim 8, characterized in that: The tensile strength of the modified lignin composite film is ≥20MPa, the elastic modulus is ≥200MPa, and the elongation at break is ≥200%.
10. Use of the modified lignin composite film according to claim 8 in making ground film, cling film, vest bag or packaging bag.
Citation Information
Patent Citations
Modified lignin compound biodegradable film and preparation method thereof
CN109181247A